O4 Conquering the growing need for SPs and coordination in simulation programs. (November 2018) - Reynolds, Karen; Gephardt, Grace; Higbee, Dena
Abstract : Who should attend: Simulation Technicians who are asked to be simulated patients/take part in simulations. Level: Introductory. Background: As traditional technology-based simulation programs gradually incorporate Simulated Participants (SPs) into their programs, the role of the Simulation Technician often grows as well. It is not uncommon that a Sim Tech is asked to step into the role of an SP on short notice to fill an absence, or to participate in a simulation as an 'extra' in the scenario. Structure of workshop and educational methods to be used: Although we all take one for the team on a regular basis, best practices established by the Association of Standardized Patient Educators (ASPE) when using SPs will be shared as a resource to help inform smoother implementation of SPs into simulation scenarios. Case templates will also be shared that help to develop a simulation scenario that encompasses the needs of both technology-based simulation and human simulation. As Sim Techs encounter a high level of involvement with SPs in programs, tips for helping with the coordination of SP programs will be discussed. Best practices of working with SPs and keeping an adequate cohort to meet learning objectives will also be discussed. Participants will compare and share how they can use technology to assist with the coordination of programs. Intended learning outcomes: Participants will feel more prepared to take part in simulations as an SP at the last minute. Participants will have a wider understanding of the value SPs can bring to the simulation. References: Simulation-Based Education in Healthcare. Standards Framework and Guidance. Association for simulated practice in healthcare (Aspin) standards for simulation-based education 2016. http://aspih.org.uk/wp-content/uploads/2017/07/standards-framework.pdf (Accessed: 31 May 2018). Association of standardized patient educators (ASPE) . http://www.aspeducators.org/standards-of-best-practice (Accessed: 31 May 2018).